혼백론에서 영혼론으로 - 이향만(Lee Hyang man) (Gatolrig sinhag gwa sa'sang, 2011)
본 연구는 동서양 영혼론을 비교하는 것을 목적으로 하고 있다. 신화와 상징적 차원에서 전통적인 중국의 혼백론과 그리스의 영혼론을 비교하고 철학적 차원에서 순자의 인성론과 아리스토텔레스의 영혼론을 비교하고 있다. 이렇게 함으로써 근대에 중국 선교 과정 안에서 이루어진 동양의 혼백론과 서양의 영혼론 만남의 문화적 배경을 고찰하려 한다. 동서양을 막론하고 영혼은 복합영혼의 형태로 생명과 의식의 근원으로서 자리 잡고 부단히 새로운 이해를 추구해 왔다. 삶과 죽음의 문제를 이해하고, 육체와 정신의 결합을 가능하게 하고 유지시켜 주는 영혼의 능력은 인간의 생명현상을 이해하는 데 없어서는 안 되는 중요한 핵심 개념이다. 역사적으로 살펴볼 때 동서양의 공통된 영혼에 대한 이해는 첫째, 영혼을 인간의 근원적인 생명작용으로 바라본 것이다. 두 번째는 영혼에 불변하는 자아의 본질이 내재되어 있다는 것이고, 세 번째는 영혼이 육체와 분리되어 불멸한다는 사고이다. 철학적 사유가 발전하면서 영혼의 기능은 생명의 근거로부터 고차원적인 의식 활동을 해명하는 데 필요하게 되었다. 육체와 상응해서 언급되는 정신이 영혼의 기능 가운데 하나이듯, 인성론과 인식론 그리고 윤리학은 모두 영혼을 바라보는 관점에 따라 나타난 분과로서 영혼론의 다른 표현이라 할 수 있다. 경험적이며 현세적인 아리스토텔레스와 순자의 영혼관은 인간본성의 보편적 관점에서 동서양의 영혼론이 충분히 소통 가능함을 보여 주고 있다. 존재론적인 측면에서 관조로 완성되는 의식의 고양 안에서 육체의 성향과 정신의 성향은 분리되어 있지 않고 조화와 통일을 이루고 있다. 인식론적으로 영혼은 인식의 주체로서 인식작용을 주관하고 대상과의 관계를 지속시킨다. 윤리적으로 영혼은 분별에 바탕을 두고 행위를 이끌며 행복을 실현한다. 그러나 영혼불멸과 관련하여 중국문화의 귀속성과 그리스 문화의 순환성은 종교적으로 서로 다른 영혼의 의례를 발전시켰다. 중국인에게 철학은 덕성의 사회적 발현을 위한 지성적 삶의 과정이다. 그리스인에게 철학은 정화를 위한 지적수행이다. 이 두 과정은 영혼의 생명성의 차이를 구분하도록 돕는다. 중국인의 영혼(지성적 활동)의 사회적인 외적 지향성과 그리스인의 관조적인 내적 지향성은 종교적인 삶에서 재현된다. 이것이 영혼관의 중요한 차이점으로 드러나고 있다. This study aims to compare different prevailing theories on the concept of soul in East and West. As a typical example the traditional Chinese and Greek theory of the soul is compared. In mythological and symbolic dimensions and in philosophical dimension, Xunzi(荀子)’s theory of personality and Aristotle’s theory of the soul is compared. By doing so, this article focuses on the background of encountering the theory of the soul of East and West through Jesuit mission in China. Regardless of East and West, soul as a source of life and consciousness has been continuously pursuing a new understanding in the form of a compound. To understand the issues of life and death, and possibility of combining of the physical and mental life, in sustaining the phenomena of human, the concept of soul is an indispensable important key aspect. First, historically it is common understanding that soul in East and West, is seen in terms of a fundamental human act of life. Second, the constant nature of the self is immanent in soul. Third, the idea of immortality of soul is seen separately from body. As the philosophical thoughts developed it became necessary to explain Soul from the basic features of human life to the high-level of awareness. As, one of the functions of the Soul is to correspond between mind and body, the theories suggested in the treatise of Human Nature, epistemology, and ethics can be considered as one of the other expressions of theory of soul. Empiricist philosophers, Aristotle and Xunzi have shown the possibility of communication from the perspective of the universal nature of human. Ontologically, no separation has been made between spirit and body in the attainment of consciousness but contemplated as inclination of harmony and unity between two. Epistemologically, soul as a cognitive subject, manage perception and continue the relationship with the object. Ethically, the realization of happiness depends on the discretion of soul. However, regarding immortality of the soul, the Chinese and Greek cultures attributes to the different religious rituals. For Chinese people, philosophy is an intellectual process of life for the social manifestations of virtue. To Greeks, philosophy is an intellective performance for a contemplative life. These two different perspectives on soul helps distinguish the different point of views on the concept of soul. The Chinese concept of soul (intellectual activity) is socially outward orientated but for Greeks its inner contemplation which is represented in their religious life. This reveals an important difference in the theory of soul. KCI Citation Count: 3